Plan de negocio para la construcción en la ciudad de Neiva de un salón de eventos (2016)
The trend today shows that the pace of life is so fast and with little time, because of this, people look for places that give them a complete and suitable service for your events. Based on the above, one might find in this business plan is an option that provides comfort, advice, coordination and a new service to meet the needs and demand. The lounge will offer renting a hall and a chapel, the latter if required, with a person who will coordinate the event during its execution, including food service, waiters, decoration, music band and valet parking. The lounge will be located just outside the city of Neiva, due to the large space required to provide good service to the guests of the event.